Pelaksanaan Prinsip Partisipasi Masyarakat pada Pemerintahan Nagari Koto Kaciak Kabupaten Agam - Putri Elfira, Adella; Frinaldi, Aldri (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to analyze the implementation of the principle of community participation in the government of Nagari Koto Kaciak, Agam Regency. Nagari government as a customary entity has great potential in implementing the principles of good governance, especially participation. However, the implementation of this principle still faces various obstacles such as low public awareness, the dominance of local elites in deliberations, and the lack of involvement of the younger generation and marginalized groups. This research uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results show that community participation in development planning, decision-making, and gotong royong activities is still not optimal. Community involvement is generally consultative and limited to certain groups. Inclusive strategies are needed through wider socialization, the use of information technology, and strengthening the role of women's and youth groups so that participation is more evenly distributed. This research recommends increasing transparency, communication, and culture-based approaches to encourage active community involvement in sustainable village development.